Molecular Diagnosis of Beak and Feather Disease in Native Brazilian Psittacines - AV Araújo; DA Andery; FC Ferreira Jr.; MC Ortiz; MVR Marques; SY Marin; DAR Vilela; JS Resende; M Resende; RV Donatti; NRS Martins (Brazilian Journal of Poultry Science, 2015)
ABSTRACT The incidence of the psittacine beak and feather disease virus (BFDV) was investigated in Brazilian native parrots with normal feathering arriving at rescue and triage centers for wild animals (CETAS, IBAMA) in the state of Minas Gerais, Brazil. BFDV DNA was investigated by previously described PCR technique for the partial amplification of BFDV ORF-1 in DNA extracts from blood, cloacal swab or liver of psittacines. Some birds provided more than one sample. Nine species of psittacines were sampled between January 2009 and October 2010. Blood (n=46) or cloacal swab (n=128) samples were obtained from psittacines immediately upon arrival at the triage centers. Liver samples were collected from necropsied birds dead on arrival (n=167). All swab samples were negative, except for one Ara ararauna individual (n=3) which blood presented the BFDV DNA. On the other hand, 11 liver samples were positive for BFDV DNA, with a prevalence of 7.8% in Amazona aestiva (n=140). No BFDV DNA was detected in the liver of Amazona amazonica (n=11), A. vinacea (n=5), A. rhodochorytha (n=4), Anodorhynchus hyacinthinus (n=3), Ara ararauna, (n=3), Aratinga leucophtalma (n=2), Guarouba guarouba (n=1) and Pionus maximiliani (n=1). In most cases, alopecia was not associated with BFDV detection in liver, and liver histopathology was inconclusive. Although all cloacal swab samples were negative, a few psittacines (n=19) that died at CETAS-Belo Horizonte were retested, and 21% were detected as positive in liver. A group of psittacines (n=16) was clinically evaluated, and despite showing feather dystrophy, all birds were negative in the cloacal swabs, except for one, which blood sample was positive (A. ararauna). The obtained sequences of the BFDV strains BH 215 and BH 732 were deposited in the GenBank (JQ649409 and JQ649410). A 98% similarity with strain sequences described in Australia, Japan, and New Zealand was observed. It is possible that these strains arrived in Brazil through the legal and illegal trade of parrots. However, it was not possible to associate BFDV infection with the geographical origin of birds and no local marker was detected. The rates of detection, although similar to other studies, indicate the tendency of a high incidence of the disease, possibly associated with stress, and high bird density and wide transmission in captivity conditions.